A topic review on probing primordial black hole dark matter with scalar induced gravitational waves - Chen Yuan; Qing-Guo Huang (iScience, 2021)
Summary: Primordial black holes (PBHs) might form from the collapse of over-densed regions generated by large scalar curvature perturbations in the radiation dominated era. Despite decades of various independent observations, the nature of dark matter (DM) remains highly puzzling. Recently, PBH DM have aroused interest since they provide an attracting explanation to the merger events of binary black holes discovered by LIGO/VIRGO and may play an important role on DM. During the formation of PBH, gravitational waves will be sourced by linear scalar perturbations at second-order, known as the scalar induced gravitational waves (SIGWs), which provides a new way to hunt for PBH DM. This topic review mainly focuses on the physics about SIGWs accompanying the formation of PBH DM.